A Review on Performance of Database Systems Azfar Inayat Khan (International Journal of Engineering and Computer Science, 2016)
Presently most of the researchers focus on works in the area of pattern recognition, computer networks, mobile computing, information security, image processing, data mining, bio inspired computing, theoretical computer science and cloud computing. Research in the area of data modelling for relational databases has trimmed down considerably.Since research in the area of data modelling for relational databases has trimmed down considerably, it has been comprehended that the fissure between user expectation and product delivered, in database systems design and development, has to be diminished. The field of modelling and design of databases is vast, with a surplus of methodologies as well as techniques, but designers need authentic guidelines that can be used for designing proficient database management systems. This paper reviews the different techniques used to perk up the performance of databases.